2014
DOI: 10.1002/ep.11971
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative absorption of NO by sodium persulfate coupled with Fe2+, Fe3O4, and H2O2

Abstract: The oxidative absorption of nitric oxide (NO) by sodium persulfate (Na2S2O8) coupled with Fe2+, Fe3O4, and H2O2 was investigated in a bubble column reactor. Moreover, the effect of temperature on NO removal has been studied. At high temperatures, Fe2+ and Fe3O4 could effectively activate persulfate to form sulfate radicals, leading to high removal efficiency of NO. About 62% and 86% of NO were removed at 75 and 90°C, respectively. Also, the optimum Fe2+ concentration for 0.2 mol L−1 persulfate was 1.0 mmol L−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The main peaks located at approximately 711.8 and 725.4 eV can be attributed to the Fe 2p 3/2 and Fe 2p 1/2 of Fe 3+ , respectively, whereas the peaks at 709.9 and 723.7 eV can be attributed to the Fe 2p 3/2 and Fe 2p 1/2 of Fe 2+ , respectively. The two residual peaks at 732.8 and 718.0 eV are satellite peaks [39]. Similarly, the highresolution Fe 2p spectra of all the samples can be fitted with six peaks (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…The main peaks located at approximately 711.8 and 725.4 eV can be attributed to the Fe 2p 3/2 and Fe 2p 1/2 of Fe 3+ , respectively, whereas the peaks at 709.9 and 723.7 eV can be attributed to the Fe 2p 3/2 and Fe 2p 1/2 of Fe 2+ , respectively. The two residual peaks at 732.8 and 718.0 eV are satellite peaks [39]. Similarly, the highresolution Fe 2p spectra of all the samples can be fitted with six peaks (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…It was observed that the NO removal efficiency decreased from 42% to 31% with the SO 2 concentration increased from 0 to 4000 ppm. The additive SO 2 could react with water via reactions (19) and (20) and subsequently, oxidation reaction of sulte ion or bisulte ion consumed SO 4 c À /cOH and produced SO 3 c À via reactions ( 21)- (23). The SO 3 c À easily reacted with water via reaction (24), producing SO 4…”
Section: Inuence Of Coexistence Gases On No Removalmentioning
confidence: 99%
“…The SO 4 c À radicals could oxidize ammonia ion in waste water which are reported as the in situ chemical oxidation (ISCO). [19][20][21] According to Nakamura T's research, 22 the persulfate ion could reduce ammonium ion into nitrogen gas, especially in the alkaline aqueous solution. According to the previous researches, it seems that the performance of pollutant removal from ue gas with the solution pH increased from 1 to 14 depends on the kind of persulfate salt.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to select an aqueous solution with a suitable reactant. Two types of agents are usually used, including a strong oxidizing agent, such as NaClO 2 , KMnO 4 , and H 2 O 2 to oxidize insoluble NO into a more soluble NO 2 , and an agent to form a complex with NO like metal chelate . Among these absorbents, ferrous chelate solution has been demonstrated as a suitable and efficient option in the denitrification process due to its high reaction rate with NO and good regeneration ability .…”
Section: Introductionmentioning
confidence: 99%